Infrared head phone / Normasliza Ad Fauzi and Rosmawati Abu - Ad Fauzi, Normasliza; Abu, Rosmawati (2003)
Infrared headphone is suitable for use in a house, office and more. It is simple and wireless. Thus it is wireless, we still can use it for a long distances. This infrared headphone consists of the main parts which is the transmitter, receiver and the load. Infrared ray is the form of rays between visible color and radio wave producing heat. The transmitter produces infrared signal that transmit by the infrared diode at the output. The infrared signal is aimed at the receiver and it will trigger its circuit. At the receiver, the infrared signal will be picked-up by the photo-transistor. Then the transistor produce charge carriers at a rate depending on the rate arrival of a cadent radiation at the junction of transistor Then if flow the receiver circuit the load headphone. We will have the same input and output signal which is audio form the radio or television.